(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article reveals the main approaches to the category of «competition», defines the features and types of competing models in a market economy, investigates a competing environment in the residential real estate market taking into account regional and structural features, identifies micro and macro factors and identifies barriers to the effective functioning of the primary The real estate market revealed that for the primary market of residential real estate is a typical model of oligopoly, and for the secondary market – a model of monopolistic on urentsiyi, analyzed the presence offers primary real estate Volyn region, proposals for directions to increase competitiveness Offers Object of residential property.